2021
DOI: 10.2147/opth.s259012
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Conductive Keratoplasty Combined with Corneal Crosslinking in Advanced Ectatic Corneal Disease

Abstract: Purpose: To assess the effectiveness of a novel treatment for patients with advanced corneal ectasia and loss of visual acuity (VA). Conductive keratoplasty (CK) is performed to improve VA followed by epithelium-on (epi-on) corneal crosslinking (CXL) to stabilize the cornea after CK. Methods: Retrospective, exploratory cohort study. Patients with keratoconus or postsurgical ectasia and best spectacle-corrected distance VA (CDVA) ≤ 20/40 were included. Conductive keratoplasty was performed (ViewPoint CK System,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Besides these investigations, other CXL protocols have been evaluated that are based on the epi-on concept, such as the CXLO protocol that uses a new sodium iodide riboflavin formulation that theoretically allows a greater level of penetration [47][48][49][50][51]. ese investigations have shown that the use of the CXLO protocol can halt the progression of ectasia and result in better visual acuity without the risk associated to epi-off CXL [47][48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides these investigations, other CXL protocols have been evaluated that are based on the epi-on concept, such as the CXLO protocol that uses a new sodium iodide riboflavin formulation that theoretically allows a greater level of penetration [47][48][49][50][51]. ese investigations have shown that the use of the CXLO protocol can halt the progression of ectasia and result in better visual acuity without the risk associated to epi-off CXL [47][48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…These investigations have shown that the use of the CXLO protocol can halt the progression of ectasia and result in better visual acuity without the risk associated to epi-off CXL [ 47 51 ]. Three of these studies show the results of this type of CXL applied one day after conductive keratoplasty (CK) [ 47 49 ]. Sinjab et al [ 49 ] observed at the end of the follow-up a mean reduction of K max with the combination of CK and CXLO of 3.8 D with the mean baseline K max value of 65.1 ± 11 D. Rechichi et al [ 52 ] evaluated the changes in the refraction and corneal aberrations in keratoconus after the selective transepithelial topography-guided photorefractive keratectomy combined with accelerated corneal crosslinking (STARE-X) and demonstrated effective results to stop the progression of keratoconus.…”
Section: Discussionmentioning
confidence: 99%